2021
DOI: 10.5435/jaaosglobal-d-21-00070
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Posterior Atlanto-occipital Dislocation With Three-part Jefferson Fracture and Subaxial Distractive Extension Injury

Abstract: No previous reports have described combined upper and lower cervical injuries caused by a contrary injury mechanism. A 44-year-old man was transferred complaining of quadriplegia caused by a rear-end collision car accident. CT and MRI findings revealed posterior atlanto-occipital dislocation (AOD) with three-part Jefferson fracture and subaxial distractive extension (DE) injury at the C3-4 and C6-7 levels. MRI showed spinal cord injury at C3-4 and C6-7, which caused quadriplegia and respiratory fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Our case has some unusual features. Similar to Chang D et al [ 11 ], the mechanism of injury producing the fracture in our case didn't correspond to the axial load mechanism first described by Jefferson. Yet, the same fracture pattern was found.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our case has some unusual features. Similar to Chang D et al [ 11 ], the mechanism of injury producing the fracture in our case didn't correspond to the axial load mechanism first described by Jefferson. Yet, the same fracture pattern was found.…”
Section: Discussionsupporting
confidence: 56%
“…Chang D et al described a three-part Jefferson fracture caused by a rear-end collision car accident. [ 11 ] A pedestrian injury and odontoid process breaking through the anterior ring was also reported to create a Jefferson fracture [ 1 , 10 ]. These studies showed other biomechanical points of view and added more spectrum of injury to the fracture.…”
Section: Discussionmentioning
confidence: 99%